Impact of Logistics Service Quality on E-shopper Satisfaction and Loyalty in Yangon: A Quantitative Study - Yee, Pan Wit; Puttibarncharoensri, Piyawan (Asian Health, Science and Technology Reports, 2024)
Myanmar’s e-commerce has been growing rapidly despite facing many challenges related to this newly established industry. Despite the nation’s enormous growth in smartphone and internet usage, the infrastructure for e-commerce logistics is still in its infancy. Since there is a limited number of studies that have been conducted on e-commerce in Myanmar, this study stands out. The purpose of this study was to determine how e-commerce logistics impact Yangon’s e-shoppers’ satisfaction and loyalty. A quantitative approach was used to collect data from 400 e-shoppers in Yangon. A multiple regression analysis was conducted to investigate the relationship between six dimensions of logistics service quality (information quality, product quality, delivery service, customer service, order condition, and reverse logistics) and customer satisfaction. The findings revealed a positive correlation between e-shopper satisfaction and loyalty as well as a statistically significant relationship between each of the six logistical service quality factors and customer satisfaction. Customer satisfaction increased the most due to reverse logistics, followed by order condition, delivery service, customer service, product quality, and information quality. For greater e-shoppers’ attraction and loyalty, retailers in Yangon should concentrate on improving all six factors of logistics service quality dimensions. They will improve satisfaction and loyalty among e-shoppers, boosting sales and profits for retailers while enhancing the shopping experience for e-shoppers.